Workplace conflicts and psychological work-related injuries: our experience in Italy - Giuseppe Taino; Andrea Battaglia; Marcello Imbriani (Journal of Health and Social Sciences)
In Europe, all countries regularly recognise mental disorders as workplace accidents (mainly post-traumatic stress disorders). However, there has been little emphasis on this emerging issue in Italy. Our discussion focuses on a recent case report regarding an employee who was affected by an acute anxiety disorder after a common workplace conflict with a coworker. Given that prolonged and unresolved relationship conflicts may result in more extreme forms of conflict known as workplace bullying, relationship conflicts should be minimised or prevented as early as possible. These conflicts can also lead to acute stress disorders, particularly in workers who are at-risk for stress disorders. To prevent psychological work-related injuries, occupational stakeholders should use assessments for work-related stress as a framework for addressing all organisational risk factors that are related to workplace relationships and conflict.